2018
DOI: 10.22159/ajpcr.2018.v11s2.28585
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and Optimization of Formulation Parameters for Selfnanoemulsifying Delivery System of Two Lipophilic and Gastrointestinal Labile Drugs Using Box-Behnken Design

Abstract: Objective: Present research work aims toward codelivery of two hydrophobic drugs, curcumin (CRM) and duloxetine hydrochloride (DXH) through self-nanoemulsifying drug delivery systems (SNEDDS). Methods:Initially, binary mixture in the ratio of 1:1 was prepared and then loaded into SNEDDS. Box-Behnken design (BBD) was adopted to develop SNEDDS. As per the optimal design, 13 SNEDDS prototypes were prepared. Castor oil, tween-80 and Transcutol P ® were used as oil, surfactant, and cosurfactant, respectively. To 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This means that the microemulsion of desired globular size with a smaller polydispersity index can be obtained and the preparation process can be successfully scaled up if sonication time as well as the amount of Smix added in the formulation, is properly controlled. This is the point of major concern as the clinical application of nanocarriers system is dependent on globular size and polydispersity index as key parameters [22][23][24]. The method used for the preparation of NLC was similar to that reported by Joshi and Patravale in 2006 with slight modifications.…”
Section: Construction Of Pseudo-ternary Phase Diagrammentioning
confidence: 94%
“…This means that the microemulsion of desired globular size with a smaller polydispersity index can be obtained and the preparation process can be successfully scaled up if sonication time as well as the amount of Smix added in the formulation, is properly controlled. This is the point of major concern as the clinical application of nanocarriers system is dependent on globular size and polydispersity index as key parameters [22][23][24]. The method used for the preparation of NLC was similar to that reported by Joshi and Patravale in 2006 with slight modifications.…”
Section: Construction Of Pseudo-ternary Phase Diagrammentioning
confidence: 94%
“…Compared to the other curcuminoids, THC shows a stronger antioxidant and anti-inflammation activity [1]. The docking analysis showed that THC might be able to inhibit amyloid precursor protein (APP) so that it has the potential to be used in the treatment of Alzheimer's disease [2]. Although THC has potent activity, the bioavailability of THC is limited due to its poor water solubility and absorption.…”
Section: Introductionmentioning
confidence: 99%